Diagnosis dan Tata Laksana Abses Peritonsil: Sebuah Tinjauan Pustaka - Azizah Nur Rahmah; Putu Ristyaning Ayu Sangging; Rani Himayani (Medula, 2023)
Peritonsillas abscess or quinsy is a disease that often appears as a complication of acute tonsillitis. Peritonsillar abscess is commonly found in twenty to forty year old adults, but it can also appears in children. The clinical manifestations of this disease are throat pain and swallowing difficulty, bad breath, referred pain on the ear, et cetera. Peritonsillar abscess is diagnosed by patient history and several tests, one of them being the aspiration of the abscess, which is the gold standard. The management of peritonsillar abscess are pharmacological treatment by giving antibiotic. Combination of penicillin and metronidazole is effective to treat peritonsillar abscess. Nonpharmacological treatment is done by gargling with warm liquid. Some complications of peritonsillar abscess are meningitis, retropharyngeal abscess, and brain abscess. One of the prevention of this disease is keeping a good oral hygiene to avoid infection.